2008
DOI: 10.1007/s00586-008-0831-6
|View full text |Cite
|
Sign up to set email alerts
|

Postural imbalance in non-treated adolescent idiopathic scoliosis at different periods of progression

Abstract: The aim of this study was to test the hypothesis that imbalance in patients with a severe deformity of the spine is associated with an increase in the sensory integration disorder. This paper is a case comparison study. Patients were divided into three groups: able-bodied (n = 53), observation (n = 23), and pre-brace (n = 26) groups. Time domain parameters (sway area, position and displacement) and structural posturographic parameters [mean distance (MD) and mean peak (MP)] were calculated from the COP excursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 35 publications
2
77
2
2
Order By: Relevance
“…Disturbance of central nervous system may impair somatosensory function and motor adaptation which lead to asymmetry of neuromuscular condition causing AIS [30,31]. Correspondingly, functional studies in AIS subjects have shown abnormalities in the postural balance and somatosensory function [32][33][34][35]. Thus, it remains plausible that LBX1 may be involved in the etiology of scoliosis through somatosensory dysfunction [15].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance of central nervous system may impair somatosensory function and motor adaptation which lead to asymmetry of neuromuscular condition causing AIS [30,31]. Correspondingly, functional studies in AIS subjects have shown abnormalities in the postural balance and somatosensory function [32][33][34][35]. Thus, it remains plausible that LBX1 may be involved in the etiology of scoliosis through somatosensory dysfunction [15].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of additional masses faced the subject to a new issue which prevented him from performing the optimal strategy; such point explained the decreased correlation with the Cobb angle due to a less appropriate response [24]. While in the literature, the correlation between the Cobb angle and the postural parameters is controversial [1,10,21,26,29], in seated position, an high correlation between these parameters was found. Even if such discrepancy may be due to the chosen parameters, the position itself seemed to be more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the Cobb angle and the postural parameters is controversial. In standing position, some authors showed an increase of the instability correlated to Cobb angle [1,26] while Shalstrand et al [27] did not show such correlation. During gait, the asymmetries computed between lower limbs are not correlated with Cobb angle [10,21,29].…”
Section: Introductionmentioning
confidence: 94%
“…Other studies have observed larger body sway area and CP displacement in AIS patients compared to their controls (Beaulieu et al, 2009;Byl et al, 1997). In the study by Beaulieu et al, AIS patients were divided into a pre-brace group (brace prescribed but not yet worn) and an observation group.…”
Section: Motor and Balance Control Impairmentmentioning
confidence: 99%